Iridoids rich fraction from Valeriana jatamansi Jones promotes axonal regeneration and motor functional recovery after spinal cord injury through activation of the PI3K/Akt signaling pathway - Wang, Yunyun; Lu, Jiachun; Xiao, Hua; Ding, Lijuan; He, Yongzhi; Chang, Cong; Wang, Wenchun (Frontiers in Molecular Neuroscience, 2024)
Valeriana jatamansi Jones (VJJ), renowned for its extensive history in traditional Chinese medicine and ethnomedicine within China, is prevalently utilized to alleviate ailments such as epigastric distension and pain, gastrointestinal disturbances including food accumulation, diarrhea, and dysentery, as well as insomnia and other diseases.Moreover, the Iridoid-rich fraction derived from Valeriana jatamansi Jones (IRFV) has demonstrated efficacy in facilitating the recuperation of motor functions after spinal cord injury (SCI). This study is aimed to investigate the therapeutic effect of IRFV on SCI and its underlying mechanism. Initially, a rat model of SCI was developed to assess the impact of IRFV on axonal regeneration. Subsequently, employing the PC12 cell model of oxidative damage, the role and mechanism of IRFV in enhancing axonal regeneration were explored using the phosphoinositide-3kinase (PI3K)/protein kinase B (Akt) signaling pathway inhibitor LY294002.Ultimately, the same inhibitor was administered to SCI rats to confirm the molecular mechanism through which IRFV promotes axonal regeneration by activating the PI3K/Akt signaling pathway. The results showed that IRFV significantly enhanced motor function recovery, reduced pathological injury, and facilitated axonal regeneration in SCI rats. In vitro experiments revealed that IRFV improved PC12 cell viability, augmented axonal regeneration, and activated the PI3K/Akt signaling pathway. Notably, the inhibition of this pathway negated the therapeutic benefits of IRFV in SCI rats. In conclusion, IRFV promote promotes axonal regeneration and recovery of motor function after SCI through activation of the PI3K/Akt signaling pathway.